2020
DOI: 10.1108/ijaim-04-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Implementing IFRS in Saudi Arabia: evidence from publicly traded companies

Abstract: Purpose The Saudi Organization for Certified Public Accountants (SOCPA) requires that International Financial Reporting Standards (IFRS), as endorsed in Saudi Arabia, be used by all listed and unlisted companies. This study aims to provide insight into IFRS implementation problems, based on a survey sent to Saudi Arabian companies listed on Tadawul, the Saudi stock market (i.e. financial hub in the Middle East). Design/methodology/approach The survey focused on the impact that IFRS conversion has had on comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…(2006) suggest that successful IFRS implementation is influenced by several factors such as country size, economic and political factors, and cultural differences. Prior studies provide evidence that local and international accounting standards are impacted to a large extent by surrounding environmental factors – social, political, legal, and economic – that may affect the accounting system in a country ( Nurunnabi et al., 2020 ). Cieslewicz (2013) indicates that people affect institutions by their culture where accounting depends on these institutions.…”
Section: Corporate Governance and Accounting Standards In Ksa Oman mentioning
confidence: 99%
See 2 more Smart Citations
“…(2006) suggest that successful IFRS implementation is influenced by several factors such as country size, economic and political factors, and cultural differences. Prior studies provide evidence that local and international accounting standards are impacted to a large extent by surrounding environmental factors – social, political, legal, and economic – that may affect the accounting system in a country ( Nurunnabi et al., 2020 ). Cieslewicz (2013) indicates that people affect institutions by their culture where accounting depends on these institutions.…”
Section: Corporate Governance and Accounting Standards In Ksa Oman mentioning
confidence: 99%
“…Further, Hope et al. (2006) and Nurunnabi et al. (2020) advocate that accounting standards, including IFRS could be influenced by different factors, including culture, political regime, country size, and economy.…”
Section: Corporate Governance and Accounting Standards In Ksa Oman mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it causes the assets of insurance companies to fall, IFRS 17 will make financial statements more transparent and make it easier for stakeholders to understand financial statements [14]. Mohammad, K., & Han (2020) [15] who surveyed companies listing on the Saudi Arabian stock market concluded that the majority of respondents supported the conversion to IFRS because it produced higher quality and transparent financial reports. Financial report transparency is essential because information asymmetry makes it difficult for consumers to evaluate the quality of insurance company policies and allows both parties to act opportunistically [16].…”
Section: Improve Reporting System Regulations To Improve Insurance Company Governancementioning
confidence: 99%
“…Economic and environmental factors, including the national culture, play a critical role in the IFRS implementation process. These factors need to be considered by all countries worldwide that are planning to adopt the IFRS (Nurunnabi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%